Facilitators and barriers of collaboration between faith communities and healthcare centres on HIV and HIV stigma - Germari Kruger; Martha T. Teijema; Eduardus A. J. G. Van der Borght; Sabine L. van Elsland; Marceline Tutu van Furth (Discover Social Science and Health)
Abstract HIV and HIV stigma remain a burden to healthcare in South Africa. One way to alleviate the load on the health system is through collaboration between healthcare workers and faith leaders. Faith communities in South Africa are perfectly positioned to support healthcare. They are integrated into the communities and have an authoritative voice. Also, healthcare workers are often religious and therefore are also part of faith communities which can be beneficial for collaborations and education on HIV topics. This research aimed to investigate the facilitators and barriers of collaborations between faith communities and healthcare centres when addressing HIV and HIV stigma. With a qualitative interpretive descriptive approach, in-depth interviews with 10 faith leaders and 8 healthcare workers were conducted in two townships of Cape Town, South Africa. The interviews were conducted in 2018, and thematically analysed. The study found facilitators and barriers of each of the six main themes namely, faith leaders are significant in medication adherence; health education about HIV is necessary but complex; faith and healthcare collaboration acknowledged but challenged; HIV stigma is prominent in communities; comprehensive role of the faith leader; and faith healing creates a complex challenge. There is a spirit of collaboration between faith leaders and healthcare workers, although the participants did not seem to know how to go about this engagement. Further research could design an intervention to facilitate such collaboration. Highlights A collaborative spirit exists between faith leaders and healthcare workers. Faith leaders play a role when healthcare workers cannot reach the community. Demands faced by faith leaders and healthcare workers cause difficulties.